FACTORS OF DEVELOPING CREATIVE SKILLS IN STUDENTS - Ismoil Ibragimovich Karimov (Journals Park Publishing, 2025)
The article discusses some of the new factors aimed at developing students' creativity skills in technology classes taught in general secondary schools.
Keywords: Creativity skills, stages of activity, complexity of objects (products), technical and technological requirements for the manufacture and use of objects (products), the degree of formation of students' creative abilities, interdisciplinary connections.